Effect of Family Support Towards Elderly Hemodialysis Patients’ Anxiety Level - Nugraha, Andri; Rahmah , Ghina Utari; Budhiaji , Purbayanti (Basic and Applied Nursing Research Journal, 2020)
One of many ways to decrease the morbidity and mortality rates on elderly hemodialysis patients is by decreasing their anxiety level on therapy sessions by family support. This research’s purpose is to find out the effect of family support on the elderly hemodialysis patients’ anxiety levels. The participants were 50 elderly hemodialysis patients. This research used a cross-sectional design. The questionnaire was adopted from House’s theory, the anxiety level was measured with Self-Rating Anxiety Scale (SAS), and ordinal regression was used for statistical analysis. The results showed that there was a significant correlation between family support and elderly hemodialysis patients’ anxiety level (P=0.026). The absence of family support affected the anxiety level from mild to moderate range. Patients without family support had 4,4 times higher chance to get mild to moderate anxiety than those with family support. Patients with chronic kidney failure who are under hemodialysis therapy treatment and having family support can increase their quality of life.